Florida Solid and Hazardous Waste Regulation Handbook: State Agency Structuring - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
The majority of Floridas state agencies have similar structures. Most agencies maintain their headquarters in Tallahassee and have regional offices throughout the state. Within each agency, there are various divisions, each with its own set of duties. Examples of such divisions include administration, permitting, enforcement, and public information. Within each division is a structure of even greater specificity—the bureau. These handle many of the divisional duties at a more local level. This is EDIS document FE455, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.